2005
DOI: 10.1007/s10646-005-0028-2
|View full text |Cite
|
Sign up to set email alerts
|

A Review and Analysis of Study Endpoints Relevant to the Assessment of “Long Term” Pesticide Toxicity in Avian and Mammalian Wildlife

Abstract: The ecological assessment of long term or reproductive effects from pesticide exposure in birds and mammals is currently seen to be problematic. In birds especially, the current test results are difficult to extrapolate to a field situation. For example, whereas a majority of laboratory studies report clutch size reductions in response to graded pesticide doses, this effect is rarely, if ever, seen in the wild in response to exposure to toxicants. Also, current laboratory tests in birds provide a very truncate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 70 publications
0
47
0
2
Order By: Relevance
“…• The current approach does not clearly state what is meant by long-term risk; this issue is considered in detail by Mineau (2005) who states that 'three issues are really rolled into one in the current EU concept of "long-term risk" of pesticides'. Presented below is a brief explanation of the three concepts: o Non-specific effects resulting from long-term or chronic exposure to pesticides -This is where there is long-term exposure which may be the result of a pesticide accumulating in tissues, a pesticide degrading slowly in the environment or when repeated applications are made.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…• The current approach does not clearly state what is meant by long-term risk; this issue is considered in detail by Mineau (2005) who states that 'three issues are really rolled into one in the current EU concept of "long-term risk" of pesticides'. Presented below is a brief explanation of the three concepts: o Non-specific effects resulting from long-term or chronic exposure to pesticides -This is where there is long-term exposure which may be the result of a pesticide accumulating in tissues, a pesticide degrading slowly in the environment or when repeated applications are made.…”
Section: Methodsmentioning
confidence: 99%
“…In a sample of 49 recent studies with mallard ducks, Mineau (2005) found that, 4 % of studies had a NOEC related to eggshell thickness but no evidence of increased breakage. Indeed, population effects in the wild tend to come about after thinning of 18 % or more (Blus, 2003).…”
Section: Examplesmentioning
confidence: 95%
See 2 more Smart Citations
“…Pesticides are vital for crop protection and human health in many parts of the world [19,20], yet due to their detrimental effects on natural ecosystems [21][22][23], we are becoming increasingly worried about their short and long term harms on the environment. A number of pesticides are in use throughout the world, but the four most important groups are insecticides, rodenticides, herbicides and fungicideseach group contains a rapidly accumulating list of persistent organic compounds capable of contaminating fresh water.…”
Section: Common Organic Contaminants In Freshwatermentioning
confidence: 99%